The Re-education of Conversos in 17th Century Amsterdam. (2nd September 2018) - Benoff, Tzvi Aryeh
ABSTRACT: During the early 17th Century, the Jewish community in Amsterdam had already developed a complex social infrastructure. As such, when Conversos from Spanish-Portuguese controlled territories moved into the community, their reintegration into a religious, Jewish society was shaped by the efforts of the various facets of the community: the Mahamad (ruling council), social organizations, and the rabbinate. Evidence of the activities of these bodies indicates that the Jewish community of Amsterdam did not conceptualize the re-education process as a specific issue or goal. As such, no special groups were formed to address the challenge as a unified whole. Instead, each of the aforementioned bodies merely focused on the repercussions of the need for education that fell under their respective sphere of influence. One of the results of this phenomenon was that certain issues, such as the practical observance of certain areas of Jewish law, were minimally addressed, if at all.